1993
DOI: 10.1002/hlca.19930760402
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between Functional Groups Part IV. The responses of four diazonium groups to adjacent electron‐rich atoms in peri‐substituted naphthalene and quinoline derivatives

Abstract: Four peri-substituted naphthalene-1-diazoniurn cations all show short attractive interactions between an electron-rich atom of the peri-substituent and the a-N-atom of the diazonium group. These are interpreted as models for incipient nucleophilic attack on a N r N bond. The diazonium group is a better acceptor of electron density 'through space' than the NO2 group, which parallels their relative 'through-u-bond' inductive effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…The pnicogen bond between two As atoms, with R(As···As)= 2.37 Å has been observed in the crystal [105] of cyclopentadienyl-AsX 2 . And finally, crystal diffraction studies [106] also support the idea of the charge transfer to a π* orbital that calculations imply is a contributing factor to the stability of the pnicogen bonds involving unsaturated systems.…”
Section: Experimental Observationsmentioning
confidence: 76%
“…The pnicogen bond between two As atoms, with R(As···As)= 2.37 Å has been observed in the crystal [105] of cyclopentadienyl-AsX 2 . And finally, crystal diffraction studies [106] also support the idea of the charge transfer to a π* orbital that calculations imply is a contributing factor to the stability of the pnicogen bonds involving unsaturated systems.…”
Section: Experimental Observationsmentioning
confidence: 76%
“…In ortho ‐unsubstituted methylthiobenzenes the methylthio group usually lies close to the benzene plane,24 but there are a few examples with torsional displacements of up to 42° 31. The only other peri ‐naphthalene containing a methylthio group is the diazonium salt 34 32 (Table 1), in which the methylthio group is rotated 65.4° out of the naphthalene plane and the sulfur atom lies at 2.938(5 Å from the α‐nitrogen atom, just slightly longer than the MeS⋅⋅⋅sp 2 ‐C separation in compound 21 for which the methylthio group lies well out of the aromatic plane. Glaser and co‐workers have demonstrated that the electron density in an aryldiazonium group is concentrated at the α‐nitrogen atom which may account for the long MeS⋅⋅⋅α‐N separation 33…”
Section: Discussionmentioning
confidence: 99%
“…[164] In order to gain some understanding of the mechanism of attack of the N N bond in the reactions of diazonium salts, the interaction of electron rich groups (O, S or N centered) with electrophilic diazonium group, placed in the peri-position of naphthalene, has been studied. [166] The sulfur species 149 displays an S···N a distance of 2.938 (5) , which is within the sum of van der Waals radii (3.3 ), however it is significantly longer than a single S À N bond (1.66-1.74 ).…”
Section: Napsn Systemsmentioning
confidence: 99%